Química e tecnologia: um aplicativo para a abordagem dos conteúdos de ácidos e bases no Ensino Médio - Xavier, Janaína Lopes (2018)
Considering the difficulties of learning in chemistry teaching, specifically acids and bases, reported in several studies, in the life experience of the researcher, and also the insertion of technology in society, this work aims to help minimize the difficulties of students in the learning of the content of acids and bases. This theme is pointed out by several authors of difficult abstraction, making it difficult for students to relate to everyday life. Thus, the relevance of this research is focused on providing an educational tool that can be used both by students and teachers, or in formal or non-formal space, that can contribute to minimize the difficulties in learning the chemical content. In view of this, the AciBase educational application was developed and was used and evaluated by students of the 1st year of High School of the Antensina Santana State College, located in the city of Anápolis, Goiás, through a questionnaire about the game and an activity on the content chemical. In this perspective, the action-research methodology was used, which is a strategy developed by teachers and researchers in the educational area, seeking to improve their knowledge and student learning. For the development of the educational application was used a methodology of design of educational applications development, named the case of hypermedia, which resulted in the educational application for AciBase smartphones. The AciBase aplicattion was developed in the Python programming language. Data collection was performed through a questionnaire that provided an analysis of the contributions of the game as a didactic strategy and through an activity on the systematic content that made possible the analysis of the conceptual appropriation through play. In the course of the analyzes, it is noticed that the students characterized the game AciBase as an important instrument in the teaching-learning process of the content of acids and bases, contributing to the appropriation of scientific knowledge. The students emphasized that the game entails a greater interest in the content, highlighting the ways in which the questions were elaborated, the ease in playing and the way to approach the content of acids and bases. In this sense, the game AciBase provided the students with motivation in search of chemical knowledge. In relation to the applied activity, it is noticed that the AciBase application contributes to the appropriation of the chemical content, but also understands that the educational application should be used as an aid tool for students and teachers in this process. The AciBase game alone does not entail learning, but its use associated with teaching methodology can become a powerful tool in this process.